Finance and Employment in Developing Countries : The Working Capital Channel - Dao, Mai Chi (IMF Working Papers; Working Paper ;, 2017)
We study the effect of external financing constraint on job creation in emerging markets and developing countries (EMDC) at the firm level by looking at a specific transmission channel - the working capital channel. We develop a simple model to illustrate how the need for working capital financing of a firm affects the link between financial constraint and the firm's job creation. We show that the effect of relaxing financial constraint on job creation is greater the smaller the firm scale and the more labor-intensive its production structure. We use the World Bank Enterprise Surveys data to test the main predictions of the model, and find strong evidence for the working capital channel of external finance on firm employment.